The Relationship between Knowledge and Compliance Consuming Iron (Fe) Tablets with Incidence of Anemia in Trimester I Pregnant Women at Bulili Public Health Center - Srilian Karyuni; Andi Bungawati; Eka Prasetia Hati Baculu (International Journal of Health, Economics, and Social Sciences (IJHESS), 2020)
Anemia in pregnancy can have an adverse impact on the mother, even during pregnancy, childbirth, as well as during the puerperium and beyond. One of the government programs to overcome anemia in pregnancy in Indonesia is by providing iron tablets (Fe) which are distributed through health centers and posyandu. The effectiveness of this program is difficult to achieve because it is influenced by the low knowledge of pregnant women about the benefits of consuming iron (Fe) tablets. Good knowledge will lead to a positive attitude in consuming iron (Fe) tablets. The purpose of this study was to determine the relationship between knowledge and adherence to consuming iron (Fe) tablets with the incidence of anemia in pregnant women in the first trimester at Bulili Public Health Center. The design of this research is analytical research. The research approach used is the Cross Sectional Study approach. This study used the Lemeshow proportion estimation technique with a total sample of 96 respondents. The test used in this study is to use the Chi - Square test. The results showed that there was a significant relationship between knowledge and the incidence of anemia in pregnant women in trimester I with p value = 0.000 (p <0.05) and there was no significant relationship between adherence to taking iron tablets (Fe) and the incidence of anemia in trimester pregnant women. I at Puskesmas Bulili with p value = 0.826 (pâ‰¥0.05). This study suggests that the midwives at the health center are expected to provide information or health counseling that is more directed at preventing anemia during pregnancy to pregnant women regarding the procedure for consuming iron (Fe) tablets to visitors to the Bulili Health Center, especially KIA (Maternal and Child Health).